Detecção de beauvericina por HPLC-DAD e MALDI-FT ICR MS em frutos de abacaxi infectados por Fusarium guttiforme - Fávero, Carolinne Simões (2024)
Pineapple is a fruit of great economic importance in fruit farming in Brazil and of high consumption worldwide, used in human and animal food, among other uses. Among the phytosanitary factors limiting the crop, fusariosis stands out, a disease caused by the fungus Fusarium guttiforme, which compromises the quality of the fruits for the market and produces an emerging mycotoxin called beauvericin (BEA), potentially harmful to the health of consumers. The importance of accurate and validated techniques for detecting BEA and establishing maximum allowable limits is urgent, as there is still no regulation in legislation in any country. Analytical techniques for the detection of mycotoxins have proven to be effective, with few studies for the detection of BEA in pineapple. Reliability in detection allows careful selection of evaluated products, ensuring food safety and economic responsibility. High Performance Liquid Chromatography (HPLC), Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR MS) combined with the matrix-assisted laser desorption/ ionization (MALDI) source and UHPLC-MS (Ultra Efficiency Liquid Chromatograph coupled to a mass spectrometer) were used to detect BEA in this work. The rice substrate was tested for the development of F. guttiforme and production of BEA, as it is a favorable environment for the development of the fungus. The HPLC-DAD results, in the first analyses, made it possible to detect BEA in the tissues of samples visibly infected with F. guttiforme (E-514), however in samples of apparently healthy tissue the mycotoxin was not detected. With MALDI-FT-ICR MS, BEA was detected in both types of samples, showing that, in addition to the greater sensitivity of the method, there is the possibility that the mycotoxin may diffuse into the apparently healthy tissues of fruits inoculated with F. guttiforme, with these tissues also being contaminated, but at limits not detectable by HPLC-DAD. The rice substrate proved to be efficient for the detection of beauvericin produced by isolates of F. guttiforme cultivated in vitro, which allows its use to produce the mycotoxin on a larger scale for subsequent studies. After these first results, UHPLC-MS was used for further analyses, however the answers were not satisfactory. In studies for the detection of BEA in pineapples previously inoculated with F. guttiforme (E-514), the analytical method that proved to be most accurate, until regulatory limits were met, was MALDI-FT-ICR MS, showing extremely high sensitivity of the method for mycotoxin detection and the ability to detect very small quantities not detected in HPLC-DAD